Empirical Evidence on Announcement Effect : The Case of Green Bond Offerings by Indian Companies - Zala, Priyanka; Vel, Rajalakshmi (Indian Journal of Research in Capital Markets, 2020)
The economy of tomorrow is dependent on the adoption of sustainable practices today. The global community is rapidly adopting to climate change needs. India is ambitious and active in climate action goals. With an estimated annual requirement of $ 960 billion for sustainable development goals (SDGs), mobilizing low-cost, long-term capital remains top priority for India. The implementation of sustainable development objectives requires judicious designing and delivering of financial products and practices by the Indian financial system. On the product front, green bonds have emerged as a suitable financing instrument for mobilizing capital for a range of environmental projects. The announcements of green bonds issues generate interesting stock performances, which are indicators of investor appreciation of sustainable development decisions of the issuing companies. The paper examined the stock market reaction to green bond offerings. In a nutshell, the paper focused on the announcement effect of green bonds offered by public and private enterprises from India through the period from 2015–2019. The study classified the green bonds based on certification. The findings showed positive abnormal returns for more than 80% of the sample of certified green bonds during the event window. The results of the study indicated that the stock market reacted positively to certified green bond announcements and negatively for few non-certified issues.